Global overview of research progress and development of precision maize planters - Li, Yang; Bingxin, Yan; Tao, Cui; Yiming, Yu; Xiantao, He; Quanwei, Liu; Zhijie, Liang; Xiaowei, Yin; Dongxing, Zhang (International journal of agricultural and biological engineering, 2016)
Maize is the most important crop for food and widely used for industrial materials, leading to its increasing demand all over the world. Precision planting is the effective method to increase maize yield. To meet the agronomic requirement of precision planting, different kinds of precision maize planters were developed. However, because of the difference of geographical environment, cropping system, farm scale and economic status among different countries, types of maize planters are various and the technologies involved are at different levels. This paper summarizes the precision maize planters currently available in the world and classifies them into four types: precision planters for tilled-land, minimum/no tilled-land, hilly & small land, and cold & arid land. Detailed characteristics have been provided for some typical precision planters and comparisons were made as to their suitability under particular working conditions. High-efficiency and high-accuracy are the main features of precision planters for tilled-land, while the ability to clean residue from seed rows and prevent planters to be blocked are the important function of precision planters for minimum/no tilled-land. To fit for hilly & small land, planters should be light-weighted and small-sized, and to warm up soil and keep moisture, planters for cold & arid land should be equipped with plastic-film mulching mechanism. Finally, developing trend of precision planting technology was analyzed and suggestions, including policy support and technical improvement, were made for developing countries to make suitable precision maize planters according to the local geographical conditions and cropping systems.